Anti-inflammatory and sedative activities of Peperomia galioides: in vivo studies in mice. Issue 10 (19th May 2021) - Wilches, Isabel; Jiménez-Castillo, Priscila; Cuzco, Nancy; Clos, M. Victoria; Jiménez-Altayó, Francesc; Peñaherrera, Eugenia; Jerves-Andrade, Lourdes; Tobar, Vladimiro; Vander Heyden, Yvan; Leon-Tamariz, Fabián; Vila, Elisabet
Abstract: Aerial parts (leaves, flowers, stem) of Peperomia galioides extract administered to mice, was used to confirm its anti-inflammatory and sedative folk uses. The anti-inflammatory activity was assessed by croton oil-induced ear oedema and myeloperoxidase (acute inflammation); cotton pellet-induced granuloma (sub-acute inflammation) and Escherichia coli Lipopolysaccharide (LPS) induced inflammation (cellular mediators). The sedative activity was studied by the pentobarbital-induced sleeping time test. Single doses (300 and 600 mg/kg; i.p.) of the extract reduced croton oil-induced ear oedema and myeloperoxidase activity. Six days administration of the extract (300 mg/kg, i.p.) to mice implanted with cotton pellets diminished granuloma formation. LPS (20 mg/kg, i.p.) enhanced plasma nitrites and TNF-α levels that were inhibited by the extract. The duration but not the onset of sleeping time was enhanced by 300 and 600 mg/kg of the extract. Our results show that P. galioides has anti-inflammatory and sedative activities in mice, which validates its traditional use. Graphical Abstract: